Socioeconomic position of Chamaerops humilis L. var. argentea Andre in the province of Taza (North East Morocco) and impact of the new Moroccan law n° 77-15 (Moroccan Official Bulletin N° 6422) on the preservation of the environment. - Lachkar, Nacima; Lamchouri, Fatima; Toufik, Hamid (Ethnobotany Research and Applications, 2020)
Abstract Background: Chamaerops humilis L. var. argentea Andre is a species that exists in abundance in the province of Taza. It is a valuable source of income for the local population, which improves living conditions and reduces poverty. Hence, the importance of highlighting and quantifying the economic interest of this variety for the local population. Methods: In this regard, for the first time, a survey was conducted in the region to assess the socio-economic importance of Chamaerops humilis, as well as the impact of the new Moroccan law n°77-15 on the ban of the use of plastic bags on its economic position. The study was carried out through a survey using 239 questionnaire sheets in five stations, conducted over two periods before (March- May, 2016) and after (November, 2016- March, 2017) the application of the new law. Results: Our study finds that Chamaerops humilis has a considerable economic value for the local population. The results showed that Chamaerops humilis is an important source of revenue through the sale of the palm heart (43.22 €/week/exploiter), and marketing of artisanal products (Doum baskets: 6.2 €/week/maker). Moreover, the application of the new law had a considerable impact on the basketry market, mainly on the marketing of Doum baskets (14.02 €/week/maker) to replace plastic bags. Conclusion: Chamaerops humilis presents a distinguished resource of income for the local population through the jobs it generates. Similarly, the application of Law n°77-15 strengthens its economic, social and environmental position, which can contribute to the achievement of local and national sustainable development. Keywords: Socio-economic Survey; Ecological alternative; Environment; Basketry; Income; Food. Résumé Contexte: Chamaerops humilis L. Var. argentea Andre est une espèce qui existe en abondance dans la province de Taza. Elle représente une source de revenus précieuse pour la population locale, qui permet d’améliorer les conditions d’existence, et réduire la pauvreté. D’où l’importance de mettre en évidence et de quantifier l’intérêt économique de cette variété pour la population locale. Méthodes: A cet égard, pour la première fois, une enquête a été menée dans la province afin d’évaluer l’importance socio-économique de Chamaerops humilis, ainsi que l’impact de la nouvelle loi marocaine n°77-15 sur l’interdiction de l’utilisation des sacs en plastique sur sa position économique. L’étude a été réalisée à travers une enquête à l’aide de 239 questionnaires dans cinq stations, menée sur deux périodes avant (mars - mai 2016) et après (novembre 2016 - mars 2017) l’application de la nouvelle loi. Résultats: Notre étude montre que Chamaerops humilis a une valeur économique considérable pour la population locale. Les résultats ont montré que Chamaerops humilis est une source importante de revenus grâce à la vente du cœur de palmier (43,22 €/semaine /exploitant), et à la commercialisation de produits artisanaux (paniers Doum : 6,2 €/semaine / fabricant). Par ailleurs, l’application de la nouvelle loi a eu un impact considérable sur le marché de la vannerie, principalement sur la commercialisation des paniers en Doum (14,02 €/semaine/monteur) pour remplacer les sacs en plastique. Conclusion: Chamaerops humilis représente une ressource de revenu importante pour la population locale grâce aux emplois qu’elle génère. De même, l’application de la loi n°77-15 vient de renforcer la position économique, sociale et environnementale de la plante, ce qui peut contribuer à la réalisation d’un développement durable local et national. Mots-clés: Enquête socio-économique; Alternative écologique; Environnement; Vannerie; Revenu; Alimentation. ملخص السياق Chamaerops humilis L. Var. argentea Andre : هو نوع نباتي موجود بكثرة في اقليم تازة و الذي يشكل مصدر دخل قيم للسكان المحليين ، مما يحسن ظروفهم المعيشية ويحد من نسبة الفقر. ومن هنا تأتي أهمية إبراز القيمة الاقتصادية لهذا النوع النباتي بالنسبة للسكان المحليين. الأساليب: في هذا الصدد، ولأول مرة، تم إجراء دراسة سوسيواقتصادية في المنطقة من أجل تقييم الأهمية الاجتماعية والاقتصادية لـ Chamaerops humilis ، وكذلك فاعلية القانون المغربي الجديد رقم 77.15 القاضي بحظر استخدام الأكياس البلاستيكية على الوضع الاقتصادي ل Chamaerops humilis. و أجريت الدراسة باستخدام 239 استمارة على مستوى خمس محطات وذلك على فترتين قبل (مارس - مايو 2016) وبعد (نوفمبر 2016 - مارس 2017) تطبيق القانون السالف الذكر. النتائج: أظهرت الدراسة أن Chamaerops humilis لها قيمة اقتصادية كبيرة بالنسبة للسكان المحليين كما بينت النتائج أن Chamaerops humilis تشكل مصدر دخل مهم بفضل بيع قلب النخيل (43.22 يورو / أسبوع / عامل) ، وتسويق المنتجات الحرفية اليدوية (سلال دوم: 6.2 يورو / أسبوع / صانع) بالإضافة إلى ذلك ، كان لتطبيق القانون الجديد تأثير كبير على سوق صناعة الدوم ، وخاصة على تسويق قفة الدوم (14.02 يورو / أسبوع / صانع) التي حلت مكان الأكياس البلاستيكية. الخلاصة: تمثل Chamaerops humilis مصدر دخل مهم للسكان المحليين بفضل الوظائف التي توفرها. كما ان تطبيق القانون رقم 77.15 عزز من الوضع الاقتصادي والاجتماعي والبيئي لهدا النوع النباتي ، والذي يتوقع أن يساهم في تحقيق التنمية المستدامة المحلية والوطنية.